Collaborative spiritual care for moral injury in the veterans Affairs Healthcare System (VA): Results from a national survey of VA chaplains. (14th April 2022) - Wortmann, Jennifer H.; Nieuwsma, Jason A.; King, Heather A.; Fernandez, Paola; Jackson, George L.; Smigelsky, Melissa A.; Cantrell, William; Meador, Keith G.
Abstract: The psychospiritual nature of moral injury invites consideration regarding how chaplains understand the construct and provide care. To identify how chaplains in the VA Healthcare System conceptualize moral injury, we conducted an anonymous online survey ( N  = 361; 45% response rate). Chaplains responded to a battery of items and provided free-text definitions of moral injury that generally aligned with key elements in the existing literature, though with different emphases. Over 90% of chaplain respondents indicated that they encounter moral injury in their chaplaincy care, and a similar proportion agreed that chaplains and mental health professionals should collaborate in providing care for moral injury. Over one-third of chaplain respondents reported offering or planning to offer a moral injury group. Separately, nearly one-quarter indicated present or planned collaboration with mental health to provide groups that in some manner address moral injury. Previous training in evidence-based and collaborative care approaches appears to contribute to the likelihood of providing integrated psychosocial-spiritual care. Results and future directions are discussed, including a description of moral injury that may be helpful to understand present areas of emphasis in VA chaplains' care for moral injury.